FOUR CHARGES OF THE ARMENIAN VARDAPETS' REGARDING THE ARMENIAN-LATIN CONSENTS IN THE XIV-XV CENTURIES - Lusine Gushchian (Гуманитарные и юридические исследования, 2021)
The article studies religious and culture activity of Armenian clergy during pervasion of the Catholic doctrine in the Armenian ecclesiastic and educational ambiance in the XIV-XV centuries. The most authoritative thinkers of the medieval Armenia, including bishops of the Syunik region (East Armenia) and the city of Kaffa (Crimea), as well as the principal of the well-known in the educated circles Gladzor University, reflected the basic aspects of dogmatic, practical and calendar differences between the Armenian and the Latin churches in their charges. Admitting the solidarity of Christianity, which formed both the Armenian and the European cultures, the authors of the charges, nevertheless, remained to be the adherents of the idea of independence of the Armenian apostolic church. Dispute with the adherents of the Catholic doctrine gave an opportunity for the new development of the Armenian religious thought, although the authors of the letters, being the representatives of Armenian religious and culture traditions, saw a menace in Catholicism' pervasion in their ambiance for the preservation of the original Armenian culture.